Dėl priebalsių t’, d’ ir k’, g’ mišimo pietų aukštaičių ir rytų aukštaičių vilniškių tarmėse - Leskauskaitė, Asta; Mikulėnienė, Danguolė (Baltistica, 1998)
ON THE MIXING OF THE CONSONANTS t’, d’ AND k’, g’ IN SOUTHERN AUKŠTAITISH AND EASTERN AUKŠTAITISH VILNIUS DIALECTS The article is an attempt to establish the area of distribution of the mixing of the apical front consonants t’, d’ and the palatal consonants k’, g’ (e. g. gẽgė ‘dėdė’, gírbo ‘dirbo’, mokinė̃lė ‘motinėlė’ etc.) and examine different versions of the origin of the phenomenon. On the basis of the analysis of copious illustrative data drawn from The Manuscript Department of History and Dialectology of the Lithuanian Language and other sources, the authors have made a map displaying the distribution of the said process. The authors of the article maintain that the mixing of consonants in South-Eastern dialects of the Lithuanian language is not a totally new development. Neither is it sporadic, though not universal. The fact that such a phenomenon can be sustained provided that it has the support of the system of the dialect has contributed to the following hypothesis: in the consonant system of South-Eastern Lithuanian subdialects the tendency of the apico-dental hard front consonants s, z, c, ʒ to correlate with the alveolar soft s", z", c", ʒ " will have caused the occurrence of a new phonological opposition, t: □",d: □", whose function was to fill a gap in the subsystem of alveolar consonants. In terms of articulation the newly formed °t", °d" show a close affinity with the aforementioned apico-palatal k", g" which used to mix with the apical front plosives t’, d’ in the past.